A 200 mm Wafer-Scale Al2O3 Photonics Waveguide Technology for UV and Visible Applications - P. Neutens; E. Mafakheri; X. Zheng; P. Helin; Z. Jafari; C. Lin; G. Jeevanandam; Nga P. Pham; S. Fan; C. Su; R. Jansen; P. Van Dorpe; et al. (IEEE Photonics Journal)
Low-loss, UV wavelength compatible Al2O3 photonic waveguides have been fabricated in a 200 mm CMOS pilot line. The Al2O3 waveguide layer optical properties and roughness were characterized by ellipsometry and AFM, respectively. Optical losses of the slab mode in the waveguide layer were studied by prism coupling. SiO2-cladded Al2O3 waveguides were patterned on 200 mm wafers and propagation losses were measured at 266, 360, 450, 532 and 638 nm wavelengths. Wafer-level measurements for 360–638 nm show an average propagation loss below 0.6 dB/cm, while die-level measurements for 266 nm yield average propagation losses between 4.3 and 14.7 dB/cm. To study the dependence of the wave propagation on processing variations, large sets of Mach-Zehnder interferometers with varying arm lengths were measured at a wavelength of 360 nm, and the coherence length of the standard 450 nm wide and 110 nm high Al2O3 waveguide was calculated to be longer than 2.2 mm.